Bridging the gap the online presentation of a select group of YouTube content creators and their followers' reception of their content - Cajucom, Benedicto Marcel IX F.
This research explores multi-layered aspects of audience engagements facilitated by YouTube content creators such as Lai Austria, Joshua Agatep, and Kazuhiko Parungao, more popularly known as Senpai Kazu. Such investigation involves strategies on content creation and “self-presentation” applied by these influencers, examining approaches and reception of audiences on their content, and its dynamics with influencer behavior and content creation. Through case study using the qualitative research method, the study investigates how influencers negotiate their public interaction, receive feedback from audiences, and develop online presence to be relatable and captivating. Furthermore, during interviews and focus group discussions, a rich understanding is built on influencer-follower dynamics, challenges on the relationship management of influencers, and strategies they employ to gain viewers’ appreciation and cultivate their trust. Data analysis underscores significance of audience feedback integration, influencers’ content creation process, and viewers’ active participation in content creation through constructive criticism to ensure a successive improvement of digital media culture. Such inquiry allows for gaining a greater sense of a complex interactive dialogue between influencers and their followers in the digital age, and, therefore, is vital for influencers, audience members, and researchers.